2017
DOI: 10.3390/ijms18102146
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Starvation-Triggered Endoplasmic Reticulum Stress, Autophagy, and Apoptosis in ARPE-19 Cells by Taurine through Modulating the Expression of Calpain-1 and Calpain-2

Abstract: Age-related macular degeneration (AMD) is a complex disease with multiple initiators and pathways that converge on death for retinal pigment epithelial (RPE) cells. In this study, effects of taurine on calpains, autophagy, endoplasmic reticulum (ER) stress, and apoptosis in ARPE-19 cells (a human RPE cell line) were investigated. We first confirmed that autophagy, ER stress and apoptosis in ARPE-19 cells were induced by Earle’s balanced salt solution (EBSS) through starvation to induce RPE metabolic stress. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 58 publications
3
39
0
Order By: Relevance
“…GRP78 and GRP94 expression was detected in our study in PAN nephrotic rats, which agrees with the findings that were reported by Inagi et al [ 19 ]. However, TAU preconditioning inhibited ER stress in nephrotic glomeruli and proximal tubules in line with previous studies on cisplatin or starvation-triggered ER damage [ 66 , 67 ].…”
Section: Discussionsupporting
confidence: 89%
“…GRP78 and GRP94 expression was detected in our study in PAN nephrotic rats, which agrees with the findings that were reported by Inagi et al [ 19 ]. However, TAU preconditioning inhibited ER stress in nephrotic glomeruli and proximal tubules in line with previous studies on cisplatin or starvation-triggered ER damage [ 66 , 67 ].…”
Section: Discussionsupporting
confidence: 89%
“…Cells were serum-starved (SS) to induce stress (Fig. S5A,B) [63][64][65] and, consistent with our findings in animal and human tissues, cells showed increased PC2 mRNA and protein expression following serum starvation (Fig. 5A-C, S5A,C) and treatment with tunicamycin (TM), an inducer of ER stress (Fig.…”
Section: Pc2 Up-regulation Protects Cells Against Stress-induced Cellsupporting
confidence: 65%
“…Calcium/calmodulin-dependent kinase II can activate NOX5 via direct phosphorylation [ 15 ]. Moreover, some studies show that crosstalk between ROS and calpain leads to the release of Ca 2+ [ 24 27 ]. The nuclear translocation of calpain-2 can be activated by increased NOX-derived ROS.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we demonstrated that taurine inhibited starvation-triggered cell damage in ARPE-19 cells [ 24 ]. However, the detailed roles of NOX (one of the main ROS sources) in EBSS-induced cell injury remain unclear.…”
Section: Introductionmentioning
confidence: 99%